2012
DOI: 10.1002/elan.201200188
|View full text |Cite
|
Sign up to set email alerts
|

On the Possibility of Uphill Intramolecular Electron Transfer in Multicopper Oxidases: Electrochemical and Quantum Chemical Study of Bilirubin Oxidase

Abstract: The catalytic cycle of multicopper oxidases (MCOs) involves intramolecular electron transfer (IET) from the Cu‐T1 copper ion, which is the primary site of the one‐electron oxidations of the substrate, to the trinuclear copper cluster (TNC), which is the site of the four‐electron reduction of dioxygen to water. In this study we report a detailed characterization of the kinetic and electrochemical properties of bilirubin oxidase (BOx) – a member of the MCO family. The experimental results strongly indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
84
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 94 publications
(212 reference statements)
17
84
0
Order By: Relevance
“…Therefore, this α value could be attributed to a mechanism where both first (outer electron transfer from the electrode) and second (intramolecular electron transfer) are rate-limiting [45]. On the one hand, these results are in excellent agreement with previously published data concerning possible changes of the rate limiting step during bioelectrocatalytic reduction of oxygen by BOx due to pH changes of the electrolyte, i.e., from heterogeneous to intramolecular ET in acidic and basic media, respectively [41,52]. On the other hand, we cannot rule out an effect of heterogeneous current density distribution due to the high surface area provided by graphene on the electrode surface [53].…”
supporting
confidence: 91%
“…Therefore, this α value could be attributed to a mechanism where both first (outer electron transfer from the electrode) and second (intramolecular electron transfer) are rate-limiting [45]. On the one hand, these results are in excellent agreement with previously published data concerning possible changes of the rate limiting step during bioelectrocatalytic reduction of oxygen by BOx due to pH changes of the electrolyte, i.e., from heterogeneous to intramolecular ET in acidic and basic media, respectively [41,52]. On the other hand, we cannot rule out an effect of heterogeneous current density distribution due to the high surface area provided by graphene on the electrode surface [53].…”
supporting
confidence: 91%
“…Single-point calculations give almost the same results as calculations with optimised structures, as is normally assumed. Experimentally, the redox potential of T1 sites with this set of ligand in various proteins is 0.3-0.7 V 33,35,89,90 (that of CueO is 0.4-0.5 V, depending on pH 91 ), showing that only the estimates obtained in a low-dielectric medium are in a reasonable range.…”
Section: Redox Potentials Of Minimised Qm and Qm/mm Structuresmentioning
confidence: 91%
“…29,31,32 Recently, it has been suggested that the reaction mechanism of the MCOs involves an uphill intramolecular electron-transfer (IET) step. 33,34,35 Many biological system contain an uphill electron-transfer step, and it has been hypothesized that this feature exists to avoid the need of optimising individual rates. 36 This suggestion can be justified by correlating observed differences in redox potentials and IET rates.…”
Section: Introductionmentioning
confidence: 99%
“…Potential values for T2 and T3 centers are more difficult to evaluate because of the many intermediates with different geometries and oxidation states that are generated in the course of O 2 reduction. [47,52,[58][59][60] Some works however reported multiple noncatalytic redox waves for MCOs in the range + 0.2 to + 0.4 V vs. Ag/AgCl, most probably because of a different enzyme orientation depending on the electrode material. [47,[61][62] At least one of these processes might be attributed to a trinuclear cluster intermediate.…”
Section: Enzymes For O 2 Reductionmentioning
confidence: 99%
“…[41,47,[63][64] An uphill intramolecular electron transfer was thus proposed, which was confirmed both by electrochemistry and quantum and molecular mechanical calculations. [60] This process is, however, still a matter of debate because the catalytic cycle involves highly oxidative species. [34,51,57] LACs are characterized by an acidic isoelectric point and an optimal activity under acidic pH.…”
Section: Enzymes For O 2 Reductionmentioning
confidence: 99%